Swamy's compilation of central civil services conduct rules - Muthuswamy; Brinda; Sanjeev (Chennai Swamy publishers, 2022)
This book contains government's order on prohibition of sexual harassment of working women, employment of children below 14 years of age and delegations to competent authorities.
Keywords: Conduct rules